(untitled) (Journal of Enam Medical College, 2013)
Background: Hypothyroidism is associated with many biochemical abnormalities including increased serum creatinine and uric acid levels. Many studies were done abroad regarding serum creatinine and uric acid levels in hypothyroid patients. We designed this study in our population for evaluation of serum creatinine and uric acid levels in hypothyroid patients. Objective: To assess serum creatinine and uric acid levels in hypothyroid patients and to find out relationship of creatinine and uric acid levels with severity of hypothyroidism. Materials and Methods: This retrospective cross sectional study to evaluate the serum creatinine and uric acid levels of hypothyroid patients and to find out relationship of hyperuricemia and hypercreatininemia with severity of hypothyroidism was done in the department of Biochemistry, Bangabandhu Sheikh Mujib Medical University, Dhaka. Results were compared with that of age and sex matched healthy euthyroid controls. Statistical analyses were performed by using SPSS for Windows version 10.0. ANOVA and unpaired t tests were done to see the significance among the groups and between groups respectively. Pearsons correlation coefficient test was done to see the correlation of serum creatinine and uric acid levels with the severity of hypothyroidism. Results: Mean serum creatinine and uric acid levels in cases were 1.38 ± 0.53 and 7.00 ± 2.54 mg/dL respectively compared to 1.01 ± 0.17 and 5.21 ± 1.35 mg/dL in controls. Conclusion: Mean serum creatinine and uric acid levels were found significantly higher in hypothyroid patients compared to controls. These findings suggest that hyperuricemia and hypercreatininemia are associated with hypothyroidism. Therefore, patients presenting with these biochemical abnormalities are recommended to be investigated to explore hypothyroidism. Journal of Enam Medical College; Vol 3 No 2 July 2013; Page 84-87 DOI: http://dx.doi.org/10.3329/jemc.v3i2.16129